2018
DOI: 10.1002/adom.201701256
|View full text |Cite
|
Sign up to set email alerts
|

Zig‐Zag Acridine/Sulfone Derivative with Aggregation‐Induced Emission and Enhanced Thermally Activated Delayed Fluorescence in Amorphous Phase for Highly Efficient Nondoped Blue Organic Light‐Emitting Diodes

Abstract: weight, flexibility as well as low-cost device production for lighting and displaying applications. In the past decades, emissive materials that can harvest both singlet (25%) and triplet (75%) excitons have attracted significant interest. Followed the phosphorescent noblemetal complexes, thermally activated delayed fluorescent (TADF) materials were emerged and were considered as an important breakthrough. [1][2][3] This is because these purely organic emitters, as inexpensive alternatives, are able to convert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…Another successful attempt in modulating the twist and lowering the Δ E ST was accomplished by Guo et al. in 2018 . Through a highly‐twisted zig‐zag conformation, the resulting TADF emitter, bis(3‐(9,9‐dimethyl‐9,10‐dihydroacridine)phenyl)sulfone (mSOAD), with acridine as donor and sulfone as acceptor, exhibits a much smaller Δ E ST of only 0.02 eV.…”
Section: Basic Design Strategies Of Three Tadf Molecular Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another successful attempt in modulating the twist and lowering the Δ E ST was accomplished by Guo et al. in 2018 . Through a highly‐twisted zig‐zag conformation, the resulting TADF emitter, bis(3‐(9,9‐dimethyl‐9,10‐dihydroacridine)phenyl)sulfone (mSOAD), with acridine as donor and sulfone as acceptor, exhibits a much smaller Δ E ST of only 0.02 eV.…”
Section: Basic Design Strategies Of Three Tadf Molecular Systemsmentioning
confidence: 99%
“…The OLEDsi ncorporating two TADF emitterse xhibit decent EQE max values of 11.7 %f or DTC-pBPSB and 5.5 %f or DTC-mBPSB, respectively.A nother successful attempti nm odulating the twist and lowering the DE ST was accomplished by . [34] Through ah ighly-twisted zig-zagc onformation, the re-sultingT ADF emitter,b is (3-(9,9-dimethyl-9,10-dihydroacridine)phenyl)sulfone (mSOAD), with acridine as donor and sulfone as acceptor, exhibits am uch smaller DE ST of only 0.02 eV.T he zigzag conformation also endows the emitter with AIE capability. Consequently,t he OLEDse xhibit ac oncentration-insensitive property,w ith the EQE max data of 14-16.6 %f or doped and non-doped devices due to the negligible p-p stacking and the bipolar property of the material.…”
Section: Large Steric-hindrance Inducedtict Tadf Moleculesmentioning
confidence: 99%
“…The DMPA-based device B1 also showed excellent efficiency of 8.05% with an FWHM of 51 nm. To the best of our knowledge, the EQEs of devices A1 and B1 are the highest among the reported deep-blue devices with CIE y <0.06 ( Tang et al., 2018 , Hu et al., 2014 , Li et al., 2018 ). Furthermore, device B1 displayed an efficiency roll-up at low luminance and extremely low-efficiency roll-off at high luminance.…”
Section: Resultsmentioning
confidence: 83%
“…Recently, Guo and co‐workers showed that the isomer of the well‐known blue TADF dye bis‐[4‐(9, 9‐dimethyl‐9,10‐dihydroacridine)‐phenyl]‐sulfone (DMAC‐DPS) obtained by linking the electron donor DMAC groups to the diphenyl sulfone (DPS) unit in meta position, exhibits AIDF properties and blue emission . The non‐doped OLED employing the bis(3‐(9,9‐dimethyl‐9,10‐dihydroacridine)phenyl)sulfone (mSOAD) achieves very remarkable performance as blue electroluminescent device with emission maximum at 488 nm and EQE of 14.0 %.…”
Section: Recent Aiegens Emitters For Non‐doped Oledsmentioning
confidence: 99%
“…The high performance of the AIDF OLED employing the isomer of DMAC‐DPS was confirmed later by Yang and co‐workers, which reported highly efficient sky‐blue solution‐processed OLEDs by using two different isomers . Besides the isomers bis‐[3‐(9, 9‐dimethyl‐9,10‐dihydroacridine)‐phenyl]‐sulfone ( m ‐ACSO2) indicated as mSOAD by Guo and co‐workers, they prepare also the bis‐[2‐(9,9‐dimethyl‐9,10‐dihydroacridine)‐phenyl]‐sulfone ( o ‐ACSO2) compound. Both molecules maintain good TADF properties with excellent solubility and AIE effect thanks to the large twisted angles between donors and acceptor unit.…”
Section: Recent Aiegens Emitters For Non‐doped Oledsmentioning
confidence: 99%